Prevention of The Dangers of Drugs and Promiscuity in The Millennial Era in Mojosarirejo Village, Diyorejo District - Rohematussoleha R; Hilmiyah Khumairotuz Zuhroh; Daffa Ade Azmi (Journal of Health Community Service, 2023)
The dangers of narcotics can threaten the health and even the lives of people who use them. Narcotics have negative consequences if abused in their use, especially if a person has become addicted to using them. This crime of circulation and abuse of narcotics, if not acted upon firmly, will cause the number of narcotics circulation to continue to increase. As a result, if this happens, it can convey a bad impact on the people and students. Socialization is one of the needs of humans, because humans are social creatures who in their daily lives need other people, and relationships between Human beings are fostered through an interpersonal relationship. Associations are also the human rights of every individual and they must be liberated, so that every human being should not be limited in association, let alone in discriminating, because it violates human rights. This method uses the method of lecture service (counseling) and discussion for data collection with pretest and posttest questionnaires for MTS & MA Darul Ulum students aged 15-17. The results of this activity are based on the evaluation obtained that the level of knowledge of students from the knowledge category is less than 50% after health education decreases to 25%, from sufficient knowledge of 20%, after education health increased to 45%, and good knowledge by 15%, the conclusion after health education increased to 30%. Therefore, it can be concluded that the level of knowledge in the prevention of drug dangers in promiscuity in Mojosarirejo village is included in the good category.